ESG and CEO turnover around the world - Colak, Gonul; Korkeamäki, Timo P.; Meyer, Niclas Oskar (Journal of Corporate Finance, 2024)
We investigate whether CEOs around the world are held accountable for stakeholder-related corporate misbehavior. The likelihood of CEO turnover increases significantly when the media coverage of the ESG incidents reaches extreme levels. CEO turnovers occur even in the cases where an incident does not lead to a stock price decline. In such cases, the board likely has a non-pecuniary motive for the turnover. This suggests that such non-pecuniary reputational concerns are an important determinant of CEO turnover decisions around the world, especially when the firm is facing intense public pressure due to stakeholder-related corporate misbehavior. This effect is more pronounced when firms are headquartered in stakeholder-oriented countries like many European countries.